Mechanism analysis and intervention strategies of the inflammatory microenvironment in traumatic spinal cord injury - Gu, Hou-yun; Lin, Fei-xiang; Liu, Ning; Xu, Can-hua (Frontiers in Immunology, 2025)
Traumatic spinal cord injury (tSCI) is a severe disabling central nervous system injury caused by external forces directly acting on the spinal cord. It can rapidly trigger the release of a large number of pro-inflammatory mediators after the injury, leading to significant neurological dysfunction and, in severe cases, paralysis. Currently, symptoms are mainly alleviated, and endogenous repair mechanisms are improved through drug intervention, surgery, stem cell transplantation, behavioral interventions, physical stimulation, and supportive therapies. However, these methods do not directly promote nerve regeneration and functional recovery. The inflammatory response after injury is an important pathological process leading to secondary damage and plays a crucial role in regulating the pathological progression of acute and chronic tSCI. However, prolonged inflammatory stimulation can further worsen the microenvironment at the injury site, leading to neurological function decline. Therefore, regulating the inflammatory microenvironment and restoring cytokine balance are expected to promote the recovery of neurological function after injury. This review summarizes the formation of the inflammatory microenvironment after tSCI, focusing on the recruitment and activation characteristics of major inflammation-related cells, and elaborates on the expression regulation, pathological effects, and impacts of key cytokines—including the interleukin family, TNF-α, and various chemokines—on neuronal survival and axonal regeneration. Additionally, we summarize multiple inflammatory signaling pathways closely related to secondary injury, such as NF-κB, JAK/STAT, and MAPK, emphasizing that these pathways are interconnected. For example, TNF-α and IL-1β can jointly activate NF-κB and MAPK to amplify the pro-inflammatory response and disrupt the blood-spinal cord barrier. Meanwhile, JAK-STAT3 amplifies inflammation while driving reactive proliferation of astrocytes and glial scar formation, thereby limiting later axonal regeneration. Based on this mutually amplifying inflammatory network, we also briefly summarize the exploratory applications of chemical antagonists, biologic agents, neuroprotective molecules, plant-derived active compounds, and hormonal interventions in regulating this microenvironment. This article aims to provide a reference for the analysis of inflammation-mediated pathological mechanisms after tSCI and the development of targeted anti-inflammatory treatment strategies.